If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5+7(2-5x)=2(9x+1)-(13x-57
We move all terms to the left:
5+7(2-5x)-(2(9x+1)-(13x-57)=0
We add all the numbers together, and all the variables
7(-5x+2)-(2(9x+1)-(13x-57)+5=0
We multiply parentheses
-35x-(2(9x+1)-(13x-57)+5+14=0
| -3(x-3)=-15 | | X-2y=52 | | 8(x-2)=6(x+10) | | 8+3(x+9)=17 | | 3(y+1)=2(2y-6) | | 0.25(y-8)=0.1(y+7) | | 1y+16=-9 | | -6(n=1)-5n=-14 | | 18x=13x+10 | | 5a+21=29 | | 3x+19=48 | | 5y-20=-7y-80 | | 8x-(x+5)3=2x+7 | | (2*3)+(x*x)=6x^2 | | (2*3)+(x*x)=6x2 | | 12s-22=50 | | 4x-2x^2=20 | | 17z-24z+15z=0 | | 4=-2x+11 | | (2a-4a+6)+a+4a+1)=22 | | (2x^2+11x-54)=0 | | (3a+2a-5)+(-a+4a+4)=7 | | (72x^2-118x+34)/(8x+2)=0 | | 0.5x+20=0.10x+5 | | n2+4n+7=0 | | 3^x-1=3^10 | | 27=k*81 | | 27=k(9*9) | | x^2-22x+126=0 | | 15x-15x=15x | | (x+38)+124+97+69=360 | | (3-5x)+140+110+62=360 |